The visibility of woman academics in the university - Marina Tomàs; Georgeta Ion; Maria Dolors Bernabeu (Sociedad Iberoamericana de Pedagogía Social, 2013)
This article explores the dimensions and conditions related to the visibility of university professorsbased on their gender using a qualitativemethodology. To do so,we used threemethods of data collectioncreated by the investigative team: a semistructured interview, discussion group and document analysis.The informationwas collected from22 interviews performedwith academics fromtwo universities, two discussiongroups of 7 participants each and analysis of institutionalwebsites, gender policies and strategic projectsfor equal opportunities.Analysis of the information indicated three large categories of causes of visibility including: causes relatedto the characteristics of the female professors themselves and cultural characteristics of the environmentin which the visibility was studied and causes derived from the function developed - teaching,investigation and management.In view of the results obtained in this study it was concluded that visibility based on gender as the objectof study contributes comprehension to university functioning and to the role of gender in the professionaldevelopment of the academics. Likewise, the present article provides a starting point for futuredevelopments on this subject and a basis for promoting possible university policies and practices in the future.